A Rare Case of Xanthogranulomatous Pyelonephritis with Spontaneous Renocolic Fistula and IVC Thrombosis. (7th September 2021) - Sforza, Daniele; Siragusa, Leandro; Ciancio Manuelli, Matteo; De Luca, Linda; Sensi, Bruno; Grande, Simona; Argirò, Renato; Nezzo, Marco; Villa, Massimo; Grande, Michele
Abstract : Xanthogranulomatous pyelonephritis (XGPN) is a rare disorder affecting the kidney which can fistulise to the colon in exceptional cases. We herein report a case of XGPN with renocolic fistula and large vessel thrombosis presenting with sepsis and pulmonary embolism. Preoperative diagnosis and strategic planning resulted in successful management. A 64-year-old woman presented to the emergency department with abdominal pain and a septic condition, corroborated by venous thromboembolism. Workup diagnosed a left renal abscess with calicocolic fistula. Scintigraphy confirmed a nonfunctioning left kidney. The patient underwent inferior vena cava filter placement and staged surgery. The first, damage control procedure was a loop ileostomy. Ten days later, when the patient's conditions improved, she underwent left nephrectomy and left colectomy with primary anastomosis. Finally, a year later, the ileostomy was closed. At follow-up, the patient was well, with unremarkable renal function. Scrupulous diagnostics, multidisciplinary decision making, and staged intervention have been key to optimal outcome.